Influence Perception Support Organization and Workload Through Organizational Climate To Work Life Balance in Unit The work of the Food and Drug Monitoring Agency in Manado (BBPOM in Manado) - Kurniawan , Agung; Rawung , Stanny; Bida , Obed (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Study carried out throughout civil servant employees of BBPOM in Manado with population totaling 73 respondents . Variable its independence is perception support organization , burden Where do you work climate organization as intervening variables , whereas variables its dependents is Work Life Balance. Measurement variables through Likert scale . Data analysis using regression multiple through SPSS application . The results of the validity test and the reliability test each show mark coefficient relation ≥ 0.30 and > 0.7, so the data is valid and can be trusted . Assumption test results classic based Based on Ordinary Leas Square (OLS), a regression model was obtained which was free from deviation assumptions and fulfill provision For get good linearity . The results show perception support organization influential positive and significant to climate organization , burden Work influential negative and significant to climate organization , perception support organization influential positive and significant on work life balance, workload Work influential negative and significant on work life balance, climate organization influential positive and significant regarding work life balance, perception support organization through climate organization influential positive and significant in a way direct on work life balance, and workload Work through climate organization influential in a way No direct positive and significant towards work life balance.